EFEKTIVITAS BADAN PENGAWAS OBAT DAN MAKANAN (BPOM) DALAM MELINDUNGI KONSUMEN DARI KOSMETIK ILEGAL - Tegar, Tegar; Claudya Fansiska; Dzulfah Mawaddah; Sintong Arion Hutapea (Causa: Jurnal Hukum dan Kewarganegaraan, 2025)
This research aims to analyze the effectiveness of supervision at the Food and Drug Supervisory Agency (BPOM) regarding consumer protection in light of the phenomenon of illegal cosmetic products. It employs normative legal research methods by examining the legal basis and authority of BPOM in overseeing the production and distribution of cosmetics. Additionally, the study investigates the factors contributing to the distribution of illegal cosmetics, such as loopholes in e-commerce platforms, high consumer demand for inexpensive products, and a lack of legal awareness. Furthermore, this research highlights the health impacts of illegal cosmetics that contain dangerous ingredients, such as mercury and hydroquinone. Ultimately, it concludes by evaluating BPOM's role in addressing the distribution of illegal cosmetics from a legal perspective, emphasizing the importance of stringent monitoring, certification processes, and law enforcement to protect public health.